GASTROINTESTINAL PARASITES ON ONE-HUMPED CAMELS IN BALI - Anissa, Rahma; Dwinata, I Made; Batan, I Wayan (Buletin Veteriner Udayana, 2023)
One-hump camel ( Camelus dromedarius ) is the most populous camel species in the world.  Camels in Bali are used for tourist attractions, namely to be ridden by tourists.  Gastrointestinal parasitic diseases . affect camel health which can reduce camel productivity and performance as well as predisposing to other infectious diseases.  This study aims to identify the types of gastrointestinal parasites present in camels so that prevention and treatment can be carried out effectively.  This study is an observational study with a cross-sectional study approach.  The samples used were feces from all camels in Bali with a total of 10 camels kept at Bali Camel Adventure, Bali Camel Safari, and Akame Camel.  Fresh feces of camels are stored in plastic pots using 10% formalin and 2% potassium bichromate separately.  Fecal examination is carried out by three methods, namely the native method, sedimentation, and flotation. The gastrointestinal parasites found are identified based on morphology according to the literature.  The data obtained are presented in a qualitative descriptive manner. The results of the study from 10 samples examined found (9/10) positive camels for nematode type gastrointestinal parasites with a prevalence reaching 90%.  The gastrointestinal nematode parasites identified in one-hump camels in Bali are Capillaria spp ., Strongyle type, Trichostrongylus spp. , Strongyloides spp. , and Trichuris spp. Given the high prevalence of gastrointestinal parasites in one-humped camels in Bali, improved husbandry management is recommended.